# Portal

You are here: Home » Content » Binomial Theorem

### Recently Viewed

This feature requires Javascript to be enabled.

# Binomial Theorem

Module by: First Last. E-mail the author

Summary: In this section, you will:

• Apply the Binomial Theorem.

Note: You are viewing an old style version of this document. The new style version is available here.

A polynomial with two terms is called a binomial. We have already learned to multiply binomials and to raise binomials to powers, but raising a binomial to a high power can be tedious and time-consuming. In this section, we will discuss a shortcut that will allow us to find (x+y) n (x+y) n without multiplying the binomial by itself n n times.

## Identifying Binomial Coefficients

In Counting Principles, we studied combinations. In the shortcut to finding (x+y) n , (x+y) n , we will need to use combinations to find the coefficients that will appear in the expansion of the binomial. In this case, we use the notation ( n r ) ( n r ) instead of C(n,r), C(n,r), but it can be calculated in the same way. So

( n r )=C(n,r)= n! r!(nr)! ( n r )=C(n,r)= n! r!(nr)!

The combination ( n r ) ( n r ) is called a binomial coefficient. An example of a binomial coefficient is ( 5 2 )=C(5,2)=10. ( 5 2 )=C(5,2)=10.

### A General Note: Binomial Coefficients:

If n n and r r are integers greater than or equal to 0 with nr, nr, then the binomial coefficient is

( n r )=C(n,r)= n! r!(nr)! ( n r )=C(n,r)= n! r!(nr)!

### Q&A:

Is a binomial coefficient always a whole number?

Yes. Just as the number of combinations must always be a whole number, a binomial coefficient will always be a whole number.

### Example 1

#### Problem 1

##### Finding Binomial Coefficients

Find each binomial coefficient.

1. ( 5 3 ) ( 5 3 )
2. ( 9 2 ) ( 9 2 )
3. ( 9 7 ) ( 9 7 )
##### Solution

Use the formula to calculate each binomial coefficient. You can also use the n C r n C r function on your calculator.

( n r )=C(n,r)= n! r!(nr)! ( n r )=C(n,r)= n! r!(nr)!
1. ( 5 3 )= 5! 3!(53)! = 543! 3!2! =10 ( 5 3 )= 5! 3!(53)! = 543! 3!2! =10
2. ( 9 2 )= 9! 2!(92)! = 987! 2!7! =36 ( 9 2 )= 9! 2!(92)! = 987! 2!7! =36
3. ( 9 7 )= 9! 7!(97)! = 987! 7!2! =36 ( 9 7 )= 9! 7!(97)! = 987! 7!2! =36
##### Analysis

Notice that we obtained the same result for parts (b) and (c). If you look closely at the solution for these two parts, you will see that you end up with the same two factorials in the denominator, but the order is reversed, just as with combinations.

( n r )=( n nr ) ( n r )=( n nr )

### Try It:

Find each binomial coefficient.

#### Exercise 1

1. ( 7 3 ) ( 7 3 )
2. ( 11 4 ) ( 11 4 )

1. 35
2. 330

## Using the Binomial Theorem

When we expand (x+y) n (x+y) n by multiplying, the result is called a binomial expansion, and it includes binomial coefficients. If we wanted to expand (x+y) 52 , (x+y) 52 , we might multiply (x+y) (x+y) by itself fifty-two times. This could take hours! If we examine some simple binomial expansions, we can find patterns that will lead us to a shortcut for finding more complicated binomial expansions.

(x+y) 2 = x 2 +2xy+ y 2 (x+y) 3 = x 3 +3 x 2 y+3x y 2 + y 3 (x+y) 4 = x 4 +4 x 3 y+6 x 2 y 2 +4x y 3 + y 4 (x+y) 2 = x 2 +2xy+ y 2 (x+y) 3 = x 3 +3 x 2 y+3x y 2 + y 3 (x+y) 4 = x 4 +4 x 3 y+6 x 2 y 2 +4x y 3 + y 4

First, let’s examine the exponents. With each successive term, the exponent for x x decreases and the exponent for y y increases. The sum of the two exponents is n n for each term.

Next, let’s examine the coefficients. Notice that the coefficients increase and then decrease in a symmetrical pattern. The coefficients follow a pattern:

( n 0 ),( n 1 ),( n 2 ),...,( n n ). ( n 0 ),( n 1 ),( n 2 ),...,( n n ).

These patterns lead us to the Binomial Theorem, which can be used to expand any binomial.

(x+y) n = k=0 n ( n k ) x nk y k = x n +( n 1 ) x n1 y+( n 2 ) x n2 y 2 +...+( n n1 )x y n1 + y n (x+y) n = k=0 n ( n k ) x nk y k = x n +( n 1 ) x n1 y+( n 2 ) x n2 y 2 +...+( n n1 )x y n1 + y n

Another way to see the coefficients is to examine the expansion of a binomial in general form, x+y, x+y, to successive powers 1, 2, 3, and 4.

(x+y) 1 =x+y (x+y) 2 = x 2 +2xy+ y 2 (x+y) 3 = x 3 +3 x 2 y+3x y 2 + y 3 (x+y) 4 = x 4 +4 x 3 y+6 x 2 y 2 +4x y 3 + y 4 (x+y) 1 =x+y (x+y) 2 = x 2 +2xy+ y 2 (x+y) 3 = x 3 +3 x 2 y+3x y 2 + y 3 (x+y) 4 = x 4 +4 x 3 y+6 x 2 y 2 +4x y 3 + y 4

Can you guess the next expansion for the binomial (x+y) 5 ? (x+y) 5 ?

See Figure 1, which illustrates the following:

• There are n+1 n+1 terms in the expansion of (x+y) n . (x+y) n .
• The degree (or sum of the exponents) for each term is n. n.
• The powers on x x begin with n n and decrease to 0.
• The powers on y y begin with 0 and increase to n. n.
• The coefficients are symmetric.

To determine the expansion on (x+y) 5 , (x+y) 5 , we see n=5, n=5, thus, there will be 5+1 = 6 terms. Each term has a combined degree of 5. In descending order for powers of x, x, the pattern is as follows:

• Introduce x 5 , x 5 , and then for each successive term reduce the exponent on x x by 1 until x 0 =1 x 0 =1 is reached.
• Introduce y 0 =1, y 0 =1, and then increase the exponent on y y by 1 until y 5 y 5 is reached.
x 5 , x 4 y, x 3 y 2 , x 2 y 3 ,x y 4 , y 5 x 5 , x 4 y, x 3 y 2 , x 2 y 3 ,x y 4 , y 5

The next expansion would be

(x+y) 5 = x 5 +5 x 4 y+10 x 3 y 2 +10 x 2 y 3 +5x y 4 + y 5 . (x+y) 5 = x 5 +5 x 4 y+10 x 3 y 2 +10 x 2 y 3 +5x y 4 + y 5 .

But where do those coefficients come from? The binomial coefficients are symmetric. We can see these coefficients in an array known as Pascal's Triangle, shown in Figure 2.

To generate Pascal’s Triangle, we start by writing a 1. In the row below, row 2, we write two 1’s. In the 3rd row, flank the ends of the rows with 1’s, and add 1+1 1+1 to find the middle number, 2. In the nth nth row, flank the ends of the row with 1’s. Each element in the triangle is the sum of the two elements immediately above it.

To see the connection between Pascal’s Triangle and binomial coefficients, let us revisit the expansion of the binomials in general form.

### A General Note: The Binomial Theorem:

The Binomial Theorem is a formula that can be used to expand any binomial.

(x+y) n = k=0 n ( n k ) x nk y k = x n +( n 1 ) x n1 y+( n 2 ) x n2 y 2 +...+( n n1 )x y n1 + y n (x+y) n = k=0 n ( n k ) x nk y k = x n +( n 1 ) x n1 y+( n 2 ) x n2 y 2 +...+( n n1 )x y n1 + y n
(11)

### How To:

Given a binomial, write it in expanded form.

1. Determine the value of n n according to the exponent.
2. Evaluate the k=0 k=0 through k=n k=n using the Binomial Theorem formula.
3. Simplify.

### Example 2

#### Problem 1

##### Expanding a Binomial

Write in expanded form.

1. (x+y) 5 (x+y) 5
2. ( 3xy ) 4 ( 3xy ) 4
##### Solution
1. Substitute n=5 n=5 into the formula. Evaluate the k=0 k=0 through k=5 k=5 terms. Simplify.
(x+y) 5 =( 5 0 ) x 5 y 0 +( 5 1 ) x 4 y 1 +( 5 2 ) x 3 y 2 +( 5 3 ) x 2 y 3 +( 5 4 ) x 1 y 4 +( 5 5 ) x 0 y 5 (x+y) 5 = x 5 +5 x 4 y+10 x 3 y 2 +10 x 2 y 3 +5x y 4 + y 5 (x+y) 5 =( 5 0 ) x 5 y 0 +( 5 1 ) x 4 y 1 +( 5 2 ) x 3 y 2 +( 5 3 ) x 2 y 3 +( 5 4 ) x 1 y 4 +( 5 5 ) x 0 y 5 (x+y) 5 = x 5 +5 x 4 y+10 x 3 y 2 +10 x 2 y 3 +5x y 4 + y 5
2. Substitute n=4 n=4 into the formula. Evaluate the k=0 k=0 through k=4 k=4 terms. Notice that 3x 3x is in the place that was occupied by x x and that y y is in the place that was occupied by y. y. So we substitute them. Simplify.
(3xy) 4 =( 4 0 ) (3x) 4 (y) 0 +( 4 1 ) (3x) 3 (y) 1 +( 4 2 ) (3x) 2 (y) 2 +( 4 3 ) (3x) 1 (y) 3 +( 4 4 ) (3x) 0 (y) 4 (3xy) 4 =81 x 4 108 x 3 y+54 x 2 y 2 12x y 3 + y 4 (3xy) 4 =( 4 0 ) (3x) 4 (y) 0 +( 4 1 ) (3x) 3 (y) 1 +( 4 2 ) (3x) 2 (y) 2 +( 4 3 ) (3x) 1 (y) 3 +( 4 4 ) (3x) 0 (y) 4 (3xy) 4 =81 x 4 108 x 3 y+54 x 2 y 2 12x y 3 + y 4
##### Analysis

Notice the alternating signs in part b. This happens because (y) (y) raised to odd powers is negative, but (y) (y) raised to even powers is positive. This will occur whenever the binomial contains a subtraction sign.

### Try It:

#### Exercise 2

Write in expanded form.

1. (xy) 5 (xy) 5
2. (2x+5y) 3 (2x+5y) 3
##### Solution
1. x 5 5 x 4 y+10 x 3 y 2 10 x 2 y 3 +5x y 4 y 5 x 5 5 x 4 y+10 x 3 y 2 10 x 2 y 3 +5x y 4 y 5
2. 8 x 3 +60 x 2 y+150x y 2 +125 y 3 8 x 3 +60 x 2 y+150x y 2 +125 y 3

## Using the Binomial Theorem to Find a Single Term

Expanding a binomial with a high exponent such as (x+2y) 16 (x+2y) 16 can be a lengthy process.

Sometimes we are interested only in a certain term of a binomial expansion. We do not need to fully expand a binomial to find a single specific term.

Note the pattern of coefficients in the expansion of (x+y) 5 . (x+y) 5 .

(x+y) 5 = x 5 +( 5 1 ) x 4 y+( 5 2 ) x 3 y 2 +( 5 3 ) x 2 y 3 +( 5 4 )x y 4 + y 5 (x+y) 5 = x 5 +( 5 1 ) x 4 y+( 5 2 ) x 3 y 2 +( 5 3 ) x 2 y 3 +( 5 4 )x y 4 + y 5

The second term is ( 5 1 ) x 4 y. ( 5 1 ) x 4 y. The third term is ( 5 2 ) x 3 y 2 . ( 5 2 ) x 3 y 2 . We can generalize this result.

( n r ) x nr y r ( n r ) x nr y r

### A General Note: The (r+1)th Term of a Binomial Expansion:

The (r+1)th (r+1)th term of the binomial expansion of (x+y) n (x+y) n is:

( n r ) x nr y r ( n r ) x nr y r
(16)

### How To:

Given a binomial, write a specific term without fully expanding.

1. Determine the value of n n according to the exponent.
2. Determine (r+1). (r+1).
3. Determine r. r.
4. Replace r r in the formula for the (r+1)th (r+1)th term of the binomial expansion.

### Example 3

#### Problem 1

##### Writing a Given Term of a Binomial Expansion

Find the tenth term of (x+2y) 16 (x+2y) 16 without fully expanding the binomial.

##### Solution

Because we are looking for the tenth term, r+1=10, r+1=10, we will use r=9 r=9 in our calculations.

( n r ) x nr y r ( n r ) x nr y r
( 16 9 ) x 169 (2y) 9 =5,857,280 x 7 y 9 ( 16 9 ) x 169 (2y) 9 =5,857,280 x 7 y 9

### Try It:

#### Exercise 3

Find the sixth term of (3xy) 9 (3xy) 9 without fully expanding the binomial.

##### Solution

10,206 x 4 y 5 10,206 x 4 y 5

### Media:

Access these online resources for additional instruction and practice with binomial expansion.

## Key Equations

 Binomial Theorem (x+y) n = ∑ k−0 n ( n k ) x n−k y k (x+y) n = ∑ k−0 n ( n k ) x n−k y k (r+1)th  (r+1)th  term of a binomial expansion ( n r ) x n−r y r ( n r ) x n−r y r

## Key Concepts

• ( n r ) ( n r ) is called a binomial coefficient and is equal to C(n,r). C(n,r). See Example 1.
• The Binomial Theorem allows us to expand binomials without multiplying. See Example 2.
• We can find a given term of a binomial expansion without fully expanding the binomial. See Example 3.

## Section Exercises

### Verbal

#### Exercise 4

What is a binomial coefficient, and how it is calculated?

##### Solution

A binomial coefficient is an alternative way of denoting the combination C(n,r). C(n,r). It is defined as ( n r )=C(n,r)= n! r!(nr)! . ( n r )=C(n,r)= n! r!(nr)! .

#### Exercise 5

What role do binomial coefficients play in a binomial expansion? Are they restricted to any type of number?

#### Exercise 6

What is the Binomial Theorem and what is its use?

##### Solution

The Binomial Theorem is defined as (x+y) n = k=0 n ( n k ) x nk y k (x+y) n = k=0 n ( n k ) x nk y k and can be used to expand any binomial.

#### Exercise 7

When is it an advantage to use the Binomial Theorem? Explain.

### Algebraic

For the following exercises, evaluate the binomial coefficient.

( 6 2 ) ( 6 2 )

15

( 5 3 ) ( 5 3 )

( 7 4 ) ( 7 4 )

35

( 9 7 ) ( 9 7 )

#### Exercise 12

( 10 9 ) ( 10 9 )

10

#### Exercise 13

( 25 11 ) ( 25 11 )

#### Exercise 14

( 17 6 ) ( 17 6 )

12,376

#### Exercise 15

( 200 199 ) ( 200 199 )

For the following exercises, use the Binomial Theorem to expand each binomial.

#### Exercise 16

(4ab) 3 (4ab) 3

##### Solution

64 a 3 48 a 2 b+12a b 2 b 3 64 a 3 48 a 2 b+12a b 2 b 3

#### Exercise 17

(5a+2) 3 (5a+2) 3

#### Exercise 18

(3a+2b) 3 (3a+2b) 3

##### Solution

27 a 3 +54 a 2 b+36a b 2 +8 b 3 27 a 3 +54 a 2 b+36a b 2 +8 b 3

#### Exercise 19

(2x+3y) 4 (2x+3y) 4

#### Exercise 20

(4x+2y) 5 (4x+2y) 5

##### Solution

1024 x 5 +2560 x 4 y+2560 x 3 y 2 +1280 x 2 y 3 +320x y 4 +32 y 5 1024 x 5 +2560 x 4 y+2560 x 3 y 2 +1280 x 2 y 3 +320x y 4 +32 y 5

#### Exercise 21

(3x2y) 4 (3x2y) 4

#### Exercise 22

(4x3y) 5 (4x3y) 5

##### Solution

1024 x 5 3840 x 4 y+5760 x 3 y 2 4320 x 2 y 3 +1620x y 4 243 y 5 1024 x 5 3840 x 4 y+5760 x 3 y 2 4320 x 2 y 3 +1620x y 4 243 y 5

#### Exercise 23

( 1 x +3y ) 5 ( 1 x +3y ) 5

#### Exercise 24

( x 1 +2 y 1 ) 4 ( x 1 +2 y 1 ) 4

##### Solution

1 x 4 + 8 x 3 y + 24 x 2 y 2 + 32 x y 3 + 16 y 4 1 x 4 + 8 x 3 y + 24 x 2 y 2 + 32 x y 3 + 16 y 4

#### Exercise 25

( x y ) 5 ( x y ) 5

For the following exercises, use the Binomial Theorem to write the first three terms of each binomial.

#### Exercise 26

(a+b) 17 (a+b) 17

##### Solution

a 17 +17 a 16 b+136 a 15 b 2 a 17 +17 a 16 b+136 a 15 b 2

(x1) 18 (x1) 18

#### Exercise 28

(a2b) 15 (a2b) 15

##### Solution

a 15 30 a 14 b+420 a 13 b 2 a 15 30 a 14 b+420 a 13 b 2

(x2y) 8 (x2y) 8

#### Exercise 30

(3a+b) 20 (3a+b) 20

##### Solution

3,486,784,401 a 20 +23,245,229,340 a 19 b+73,609,892,910 a 18 b 2 3,486,784,401 a 20 +23,245,229,340 a 19 b+73,609,892,910 a 18 b 2

#### Exercise 31

(2a+4b) 7 (2a+4b) 7

#### Exercise 32

( x 3 y ) 8 ( x 3 y ) 8

##### Solution

x 24 8 x 21 y +28 x 18 y x 24 8 x 21 y +28 x 18 y

For the following exercises, find the indicated term of each binomial without fully expanding the binomial.

#### Exercise 33

The fourth term of (2x3y) 4 (2x3y) 4

#### Exercise 34

The fourth term of (3x2y) 5 (3x2y) 5

##### Solution

720 x 2 y 3 720 x 2 y 3

#### Exercise 35

The third term of (6x3y) 7 (6x3y) 7

#### Exercise 36

The eighth term of (7+5y) 14 (7+5y) 14

##### Solution

220,812,466,875,000 y 7 220,812,466,875,000 y 7

#### Exercise 37

The seventh term of (a+b) 11 (a+b) 11

#### Exercise 38

The fifth term of (xy) 7 (xy) 7

##### Solution

35 x 3 y 4 35 x 3 y 4

#### Exercise 39

The tenth term of (x1) 12 (x1) 12

#### Exercise 40

The ninth term of (a3 b 2 ) 11 (a3 b 2 ) 11

##### Solution

1,082,565 a 3 b 16 1,082,565 a 3 b 16

#### Exercise 41

The fourth term of ( x 3 1 2 ) 10 ( x 3 1 2 ) 10

#### Exercise 42

The eighth term of ( y 2 + 2 x ) 9 ( y 2 + 2 x ) 9

##### Solution

1152 y 2 x 7 1152 y 2 x 7

### Graphical

For the following exercises, use the Binomial Theorem to expand the binomial f(x)= (x+3) 4 . f(x)= (x+3) 4 . Then find and graph each indicated sum on one set of axes.

#### Exercise 43

Find and graph f 1 (x), f 1 (x), such that f 1 (x) f 1 (x) is the first term of the expansion.

#### Exercise 44

Find and graph f 2 (x), f 2 (x), such that f 2 (x) f 2 (x) is the sum of the first two terms of the expansion.

##### Solution

f 2 (x)= x 4 +12 x 3 f 2 (x)= x 4 +12 x 3

#### Exercise 45

Find and graph f 3 (x), f 3 (x), such that f 3 (x) f 3 (x) is the sum of the first three terms of the expansion.

#### Exercise 46

Find and graph f 4 (x), f 4 (x), such that f 4 (x) f 4 (x) is the sum of the first four terms of the expansion.

##### Solution

f 4 (x)= x 4 +12 x 3 +54 x 2 +108x f 4 (x)= x 4 +12 x 3 +54 x 2 +108x

#### Exercise 47

Find and graph f 5 (x), f 5 (x), such that f 5 (x) f 5 (x) is the sum of the first five terms of the expansion.

### Extensions

#### Exercise 48

In the expansion of (5x+3y) n , (5x+3y) n , each term has the form ( n k ) a nk b k , where k ( n k ) a nk b k , where k successively takes on the value 0,1,2,...,n. 0,1,2,...,n. If ( n k )=( 7 2 ), ( n k )=( 7 2 ), what is the corresponding term?

##### Solution

590,625 x 5 y 2 590,625 x 5 y 2

#### Exercise 49

In the expansion of ( a+b ) n , ( a+b ) n , the coefficient of a nk b k a nk b k is the same as the coefficient of which other term?

#### Exercise 50

Consider the expansion of (x+b) 40 . (x+b) 40 . What is the exponent of b b in the kth kth term?

k1 k1

#### Exercise 51

Find ( n k1 )+( n k ) ( n k1 )+( n k ) and write the answer as a binomial coefficient in the form ( n k ). ( n k ). Prove it. Hint: Use the fact that, for any integer p, p, such that p1,p!=p(p1)!. p1,p!=p(p1)!.

##### Solution

( n k1 )+( n k )=( n+1 k ); ( n k1 )+( n k )=( n+1 k ); Proof:

( n k1 )+( n k ) = n! k!( nk )! + n! ( k1 )!( n( k1 ) )! = n! k!(nk)! + n! ( k1 )!( nk+1 )! = ( nk+1 )n! ( nk+1 )k!(nk)! + kn! k( k1 )!( nk+1 )! = ( nk+1 )n!+kn! k!( nk+1 )! = ( n+1 )n! k!( ( n+1 )k )! = ( n+1 )! k!( ( n+1 )k )! =( n+1 k ) ( n k1 )+( n k ) = n! k!( nk )! + n! ( k1 )!( n( k1 ) )! = n! k!(nk)! + n! ( k1 )!( nk+1 )! = ( nk+1 )n! ( nk+1 )k!(nk)! + kn! k( k1 )!( nk+1 )! = ( nk+1 )n!+kn! k!( nk+1 )! = ( n+1 )n! k!( ( n+1 )k )! = ( n+1 )! k!( ( n+1 )k )! =( n+1 k )

#### Exercise 52

Which expression cannot be expanded using the Binomial Theorem? Explain.

• ( x 2 2x+1) ( x 2 2x+1)
• ( a +4 a 5) 8 ( a +4 a 5) 8
• ( x 3 +2 y 2 z) 5 ( x 3 +2 y 2 z) 5
• (3 x 2 2 y 3 ) 12 (3 x 2 2 y 3 ) 12
##### Solution

The expression ( x 3 +2 y 2 z) 5 ( x 3 +2 y 2 z) 5 cannot be expanded using the Binomial Theorem because it cannot be rewritten as a binomial.

## Glossary

binomial coefficient:
the number of ways to choose r objects from n objects where order does not matter; equivalent to C(n,r), C(n,r), denoted ( n r ) ( n r )
binomial expansion:
the result of expanding (x+y) n (x+y) n by multiplying
Binomial Theorem:
a formula that can be used to expand any binomial

## Content actions

### Give feedback:

My Favorites (?)

'My Favorites' is a special kind of lens which you can use to bookmark modules and collections. 'My Favorites' can only be seen by you, and collections saved in 'My Favorites' can remember the last module you were on. You need an account to use 'My Favorites'.

| A lens I own (?)

#### Definition of a lens

##### Lenses

A lens is a custom view of the content in the repository. You can think of it as a fancy kind of list that will let you see content through the eyes of organizations and people you trust.

##### What is in a lens?

Lens makers point to materials (modules and collections), creating a guide that includes their own comments and descriptive tags about the content.

##### Who can create a lens?

Any individual member, a community, or a respected organization.

##### What are tags?

Tags are descriptors added by lens makers to help label content, attaching a vocabulary that is meaningful in the context of the lens.

| External bookmarks